2020
DOI: 10.1007/s42452-020-2701-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of collagen-based electrospun scaffolds containing silver sulphadiazine and Aspalathus linearis extract for potential wound healing applications

Abstract: Bone, skin and soft tissue chronic wounds emanating from burns or bacterial infections which persist due to prolonged tissue inflammation contribute to a delay in wound healing. Electrospun biomimetic scaffolds produced from biodegradable polymers have proven to be a better alternative due to their large surface area to volume ratio and ability to release the drug directly to the wound surface allowing fast and sustained absorbance over the affected wound area. In this study, poly lactic acid (PLA) (20% w/v) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The in vivo assay also confirmed that the PLA and PLA/PVA/SA electrospun membranes significantly enhanced wound healing compared to commercially available gauzes [26]. Ilomuanya et al, designed PLA and collagen-PLA electrospun fibrous scaffolds with antibacterial activity for wound healing applications [12]. They used silver sulphadiazine (Ag+S) and Aspalathus linearis (AL) fermented extract to improve antibacterial properties and cellular biocompatibility.…”
Section: Application Of Pla-based Electrospun Fibers In Wound Healingmentioning
confidence: 81%
See 3 more Smart Citations
“…The in vivo assay also confirmed that the PLA and PLA/PVA/SA electrospun membranes significantly enhanced wound healing compared to commercially available gauzes [26]. Ilomuanya et al, designed PLA and collagen-PLA electrospun fibrous scaffolds with antibacterial activity for wound healing applications [12]. They used silver sulphadiazine (Ag+S) and Aspalathus linearis (AL) fermented extract to improve antibacterial properties and cellular biocompatibility.…”
Section: Application Of Pla-based Electrospun Fibers In Wound Healingmentioning
confidence: 81%
“…The electrospinning method promotes the modulation of the physical and mechanical properties of fibers through tuning the corresponding variables. These superior aspects are the main factors to attend to in designing advanced wound dressings that can mimic the native tissue environment and enhance healing of the wound [3,12,28,50].…”
Section: Electrospinning Process and Its Advantages For Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Soap Skin irritancy Skin sebum content Trans-epidermal water loss Safety evaluation called lichen simplex chronicus or neurodermatitis. This presents initially with erythema (redness), excoriations, darkening of the affected portion, and consequently leathery (thickening) of the skin from prolonged itching [11,[13][14].…”
Section: Introductionmentioning
confidence: 99%